E-Learning Model for Technical and Vocational Education: In Vocational High School - ., Seninil; Bruri Triyono, Mochamad; Dahar Minghat, Asnul; Dwi Surjono, Herman; Salina Mustakim, Siti (International Journal of Engineering and Technology, 2018)
E-learning has been to be a very popular choice in the 21st century education world. E-learning able to meet a variety of learning needs tailored to each level of education. E-learning makes it easy for a teacher to give lessons to students without being bound by space and time anymore. Students can receive subject matter anywhere and anytime while at home, at school, and at work. Students can take advantage of discussion forums to discuss remotely through the use of collaborative learning tools available in e-learning. The goal to be achieved is to know the e-learning model for vocational education, namely vocational high school (SMK). In particular, this paper reviews the technical literature on the concept of e-learning, e-learning models, and the development of e-learning models in the context of TVE. Regarding e-learning studies, journal articles, opinion papers, conceptual papers, etc. are analyzed for content related to the e-learning model on TVE. It was concluded that the use of e-learning in vocational education such as Vocational High Schools was needed to assist teachers in improving the learning process. E-learning needs for vocational high schools as an effective learning media adapted to the vocational characteristics of each school.Â